2019
DOI: 10.11124/jbisrir-2017-003654
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of women who have planned unassisted home births: a systematic review protocol

Abstract: Review question/objective: The objective of this review is to identify, appraise and synthesize the qualitative evidence on the experiences of women in high resource countries who have planned unassisted home births. This qualitative review aims to answer the following question: what are the experiences of women who have planned unassisted home births?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Previous syntheses of this research suggest that women make this choice, for reasons of autonomy, choice, and control over their own bodies, due to midwives and current maternity services [ 32 , 87 ]. This body of literature is currently being further synthesized in order to supplement previous research in this area [ 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous syntheses of this research suggest that women make this choice, for reasons of autonomy, choice, and control over their own bodies, due to midwives and current maternity services [ 32 , 87 ]. This body of literature is currently being further synthesized in order to supplement previous research in this area [ 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frequently, birth parents choose to birth in a maternity suite or in hospital under the expert care of midwives or obstetricians 27. However, for this review, we specifically consider OOHBs where emergency ambulance clinicians are called for assistance.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The main reason for exclusion at this stage was that the study did not meet the 6/10 threshold for inclusion as outlined in the protocol (see Appendix III). 24 A final total of 6 records 13,[30][31][32][33][34] were included in the systematic review.…”
Section: Study Inclusionmentioning
confidence: 99%
“…Studies published in English were included as per the protocol. 24 Our search strategies were not limited to English-only studies, and one non-English study was identified during the screening process. Studies published from database inception to March 2022 were included in this review to ensure that all experiences of planned unassisted birth were captured.…”
Section: Search Strategymentioning
confidence: 99%